Perancangan Enterprise Architecture Aplikasi Manage Personal Finance dengan Framework TOGAF dan PEAF - Mangapul Siahaan; Yulsen Yulsen; Muhammad Dody Firmansyah (Sekawan Institut, 2026)
The development of information technology encourages the use of the Manage Personal Finance application as a more systematic and data-driven financial management tool. However, in prac-tice, the application still faces various problems, such as an unintegrated financial recording pro-cess, limited system architecture documentation, and the absence of an enterprise architecture framework that best suits business needs and long-term development. These problems have the potential to cause the system to be out of alignment with the organization's strategic objectives and difficult to develop sustainably. This study aims to: (1) design an enterprise architecture for the Manage Personal Finance application using the TOGAF ADM 9.2 framework; (2) produce an integrated business, data, application, and technology architecture blueprint; and (3) compare the effectiveness of the TOGAF and PEAF frameworks quantitatively based on five indicators, namely alignment with business needs, completeness of documentation, implementation speed, scalability, and resource requirements. The research method used is the design of an enterprise architecture based on TOGAF ADM, followed by a comparative analysis of the PEAF framework as an alternative, more pragmatic approach. The results of the study indicate that TOGAF excels in 3 out of 5 indicators (60%), namely business needs alignment, completeness of documentation, and system scalability, while PEAF excels in 2 indicators (40%), namely speed of implementation and resource efficiency. These findings indicate that TOGAF is more suitable for the development of Manage Personal Finance applications that have high complexity and long-term orientation. Thus, this study provides an empirical contribution in selecting the optimal enterprise architec-ture framework for the development of integrated and sustainable financial systems.